Is inflammation a consequence of extracellular hyperosmolarity? - Pooya Mohammad; Guais Adeline; Schwartz Laurent; Abolhassani Mohammad (BMC, 2009)
Abstract Background There are several reports suggesting that hyperosmolarity induces inflammation. We recently showed that Dextran Sodium Sulfate causes inflammatory bowel disease due to hyperosmolarity. The aim of this study was to confirm the link between hyperosmolarity and inflammation by assessing osmolarity values in vivo during inflammation, compare the inflammatory potential of different osmotic agents and finally study the long-term consequences of hyperosmolarity on cell fate. Methods Osmotic pressures were measured in inflammatory liquids withdrawn from mice subjected to inflammation caused either by subcutaneous injection of Bacille Calmette-Guérin (BCG) or Freund adjuvant. Three epithelial cell lines (HT29, T24 and A549) were exposed up to 48 hours to increasing osmolarities (300, 600, 900 mOsm) of chemically inert molecules such as Mannitol, Propylene Glycol, and Glycerol and inflammatory response was assessed by Enzyme Linked ImmunoSorbent Assay (ELISA) and RNA Protection Assay (RPA). Finally, normal mouse macrophages were exposed to hyperosmotic conditions for long-term culture. Results The inflammation caused either by BCG or Freund adjuvant is correlated to hyperosmolarity in inflammatory liquids. The exposure of cells to the different compounds, whatever their molecular weight, has no effect on the secretion of cytokines as long as the osmolarity is below a threshold of 300 mOsm. Higher osmolarities result in the secretion of proinflammatory cytokines (Interleukin-8, Interleukin-6, Interleukin-1β and Tumor Necrosis factor-α). Long-term hyperosmotic culture extends normal macrophage half-life, from 44 days to 102 days, and alters the expression of p53, Bcl-2 and Bax. Conclusion The present study further suggests inflammation and hyperosmolarity are closely related phenomena if not synonymous.